2018
DOI: 10.4171/jfg/68
|View full text |Cite
|
Sign up to set email alerts
|

Frequency dependence of Hölder continuity for quasiperiodic Schrödinger operators

Abstract: We prove estimates on the Hölder exponent of the density of states measure for discrete Schrödinger operators with potential of the form V (n) = λ ( (n+1)β − nβ ), with λ large enough, and conclude that for almost all values of β , the density of states measure is not Hölder continuous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
3
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…This generalizes the results in [12]. Munger [34] considered the frequency of constant type, i.e. α κ = [κ; κ, κ, · · · ].…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…This generalizes the results in [12]. Munger [34] considered the frequency of constant type, i.e. α κ = [κ; κ, κ, · · · ].…”
Section: Introductionsupporting
confidence: 83%
“…(3) For α = α κ , the first equality in (iv) is (1.5) ( see [34]); for any irrational α, the third equality in (iv) is (1.4) (see [27,19,28]). We state them here for comparison.…”
Section: Remarkmentioning
confidence: 99%
See 1 more Smart Citation
“…This generalizes the results in [7]. Munger [24] gave estimation on the optimal Hölder exponent of N ακ,λ and obtained asymptotic formula for it. For λ > 20, Qu [27] obtained the dimension formula of N ακ,λ similar with (1.1), he also showed that N ακ,λ is exact-dimensional and obtained similar asymptotic behavior as (1.2).…”
Section: Introductionsupporting
confidence: 82%
“…and the lower densityd * (α) := lim inf K→∞ 1 K K k=1 a k < ∞ of α.Namely, still assuming λ > 24, Munger[183] has also shown that N λ,α is Hölder continuous if d * (α) is finite, and it is not Hölder continuous if d * (α) is infinite. Transport Exponents.…”
mentioning
confidence: 99%